(untitled) (UUM Journal of Legal Studies, 2021)
The relationship between parties in corporate world is essential in order to addressing business disagreements. Where it is focusing on the language of business contract per se. Despite various dispute solutions and legal provisions on corporate, company and shareholder rights, all the parties concern are still facing some challenges. Mediation method is one of the alternative dispute resolutions for those who seeks justice without undergo the court proceeding. It is a swift and inexpensive form of dispute resolution. Mediator’s role is to facilitate the disputing parties, and utilizes both joint and private sessions to assist them to achieve consensus. In view of the economic interest, and with a vision to maintain their business relation, a private settlement is preferred between them. This study is using the doctrinal and comparative research methods. In which, this study is comparing the pertinent literature on jurisdiction of the court and Mediation Bodies in terms of Corporate / Company / Shareholders. The discoveries of this study are vital in describing the pros and cons of mediation practices and how it reflects justice to the Malaysian society.